Kepemimpinan Visioner Kepala Madrasah MIN 13 Ngawi dalam Meningkatkan Mutu Pendidikan - M. Hanif Satria Budi (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2020)
Quality education is closely related to leaders. Leaders who have a vision, are creative, innovative will be able to advance education in Indonesia. With the advancement of education, the community will be satisfied with the needs needed. This study aims to determine the principal's policy in achieving the vision, mission, educational goals and to find out the visionary leadership in implementing the vision for the advancement of education To get good findings, researchers used a qualitative approach. Data collection is done by using interviews, observation, and documentation. The research informants are the school principal and all vice-principals. This research found that visionary leadership was carried out maximally. This can be seen as follows: 1) Formulating the Vision . The formulation of this vision is based on the principal's personal values. The school principal changed the vision of the school to become more focused. Going forward by evaluating activities once a semester. Hold weekly meetings to listen to suggestions or complaints from teachers. The principal also makes short and long term programs. That way the planned activities will go according to plan. 2) Apply the Vision. In applying this vision the school principal does things like giving birth to 5 madrasa principles. a) Faithful, b) Orderly and disciplined, c) Ahlakul Karimah, d) Ukhuwah Islamiyah, e) Competent. In addition, in applying the vision the school principal also has short, medium, and long-term plans.